A new species of Anchylorhynchus Schoenherr (Coleoptera: Curculionidae) from the Amazon, with a record of a new host palm for the genus - Valente, Roberta De Melo; de Medeiros, Bruno Augusto Souza (Zootaxa, 2013)
Anchylorhynchus vanini sp. nov. from the Amazon is described, including the mouthparts and male genitalia. The new species is compared with similar species within the genus and the key to the species of Anchylorhynchus provided by Vaurie (1954) is modified to include the new species. Adult specimens were collected in flowers of the palm Syagrus vermicularis Noblick and additional collections in other palms species suggest that this association is specific. This is the first record of the palm Syagrus vermicularis as host for a species of Anchylorhynchus.